(untitled) (Colombia Medica, 2006)
Background: At present there are few effective antimalarial drugs, amodiaquine is one of them; however, its use has been restricted by previous information about hematic and hepatic toxicity when it is administered as prophylactic at doses greater than 1,500 mg. But at therapeutic doses, the side effects are either slight or of moderate intensity and include nausea, vomit and pruritus. Objective: To evaluate the hepatic and hematic toxicity of amodiaquine administered at doses and time recommended for treatment of uncomplicated Plasmodium falciparum malaria. Methods: Longitudinal design with no blind determination of the effect. A total of 57 patients were included and followed up for 10 days (clinical-parasitological evaluation). Results: Hematic and hepatic variables showed slight alteration previous treatment and were normal postreatment. Therapeutic efficacy of amodiaquine was 100%. All variables were normal at days 5 and 10, suggesting absence of toxic effects imputable to amodiaquine. The side effects were few, slight and disappeared completely at day 10. Conclusions: Amodiaquine administered at doses (25 mg/kg weight) and time (3 days) established for treatment of uncomplicated Plasmodium falciparum malaria is safe, it did not show neither hematic nor hepatic toxicity.